Cytotoxic Triterpenoid Saponins from the Stems of Gordonia longicarpa - Tang, Jia; Yu, Lei; Fu, Huizheng; Li, Chuangjun; Yang, Jingzhi; Zhou, Wanqi; Chen, Xiaoguang; Zhang, Dongming (Planta Medica, 2013)
Nine new triterpenoid saponins named longicarposides A–I (1–9), together with three known saponins (10–12), were isolated from the stems of Gordonia longicarpa. The structures of the saponins were elucidated by a combination of 1D and 2D NMR techniques, mass spectrometry, and chemical methods. They were characterized to be oleanane-type saponins with sugar moieties linked to C-3 of the aglycone. Cytotoxic activities of these saponins were evaluated against five human tumor cell lines (HCT-8, Bel-7402, BGC-823, A549, and A2780) by using the MTT in vitro assay. Compounds 5, 7, 8, 10, and 11 exhibited potent cytotoxic activity with IC50 values of 1.42–8.42 µM, while 6, 9, and 12 showed selective cytotoxic activity toward the tested cell lines.
Keywords: Gordonia longicarpa; Theaceae; triterpenoid saponins; longicarposides A–I; cytotoxic activity